The Impact of Children's Access to Public Health Insurance on Their Cognitive Development and Behavior - Marie C. Hull; Ji Yan (Institute of Labor Economics (IZA), 2024)
While a large literature examines the immediate and long-run effects of public health insurance, much less is known about the impacts of total program exposure on child developmental outcomes. This paper uses an instrumental variable strategy to estimate the effect of cumulative eligibility gain on cognitive and behavioral outcomes measured at three points during childhood. Our analysis leverages substantial variation in cumulative eligibility due to the dramatic public insurance expansions between the 1980s and 2000s. We find that increased eligibility improves child cognitive skills and present suggestive evidence on better behavioral outcomes. There are notable heterogeneous effects across the subgroups of interest. Both prenatal eligibility and childhood eligibility are important for driving gains in the test scores at older ages. Improved child health is found to be a mediator of the impact of increased eligibility.
Keywords: H51; I13; I38; J13; J24; 330; Medicaid; state children's health insurance program; health insurance; human capital; cognitive development; non-cognitive skills